Medication communication between nurses and patients during nursing handovers on medical wards: A critical ethnographic study - Munira Noman Ghannam Al-Saidi, Abeer Rubayyi Almatrafi, Ghanem Turki Mutee Al-Dhafiri, Eidah Barboot Muhanh Alenizy, Mariam Mohammed Alyas Alenezi, Fatima Daghim Al-Shammari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Effective communication is crucial for safe medication management, particularly during handover processes where nurses exchange critical patient information. While previous studies have explored handover practices generally, little attention has been given to the specific dynamics of medication communication and power relations among nurses and patients during handover.Objectives: This study aims to investigate the dominant and submissive communication styles and power dynamics surrounding medication communication during handover among healthcare professionals and patients.Design: Employing a critical ethnographic approach, this research delves into the social and power dynamics inherent in medication communication during handover.Settings: The study was conducted in a tertiary care hospitalParticipants: All registered nurses working in the hospital's medical wards during the study period were eligible participants. Patients who could actively engage in discussions about their medication management were also included. A total of 60 nurses and 20 patients provided written consent and participated in the study.Methods: The research utilized participant observations, field interviews, video recordings, and reflexive focus groups to capture the nuances of medication communication during handover. Data analysis was guided by a critical discourse analytic framework.Results: The study revealed that nurse-led handovers predominantly emphasized organizational and biomedical discourses, often neglecting in-depth discussions on medication effectiveness. Patient involvement during bedside handovers promoted a collaborative approach to medication communication, although nurses exercised discretion in discussing sensitive information away from the bedside. Communication breakdowns were observed during patient transfers between wards due to inadequate information exchange.Conclusions: The findings suggest a need for a shift in organizational control of handover practices to empower bedside nurses in medication communication. Providing designated meeting spaces and encouraging open communication during handovers can enhance the effectiveness of medication information exchange and improve patient safety.